A systematic review and meta-analysis of second-line therapies for treatment of mesothelioma. (August 2018) - Petrelli, Fausto; Ardito, Raffaele; Conti, Barbara; Coinu, Andrea; Cabiddu, Mary; Ghilardi, Mara; Borgonovo, Karen; Barni, Sandro; Ghidini, Antonio
Abstract: Introduction: Advanced malignant pleural mesothelioma (MPM) is generally treated with platinum/pemetrexed-based first-line therapy. Once the disease progresses, evidence for the efﬁcacy of palliative treatments is lacking, and platinum re-challenge or single-agent chemotherapy are commonly used. To assess the effects of cytostatic or targeted therapy for treating MPM, we performed a systematic review and meta-analysis. Material and methods: PubMed, the Cochrane Library, and Embase databases were searched to identify published articles on second-line treatments for recurrent or advanced mesothelioma. Inclusion criteria were publication in the English language, describing clinical trials with 20 or more patients, and evaluability for efficacy and for receiving second-line systemic therapies. Data were pooled using number of events/number of evaluable patients, median overall survival (OS) and progression-free survival (PFS), according to a fixed or random effect model. Pooled median OS was the primary endpoint. Results: A total of 49 eligible studies (n = 3938 patients; range, 12–400) were identified. Median progression-free survival (PFS) was 3.4 months (95%CI 2.87–3.93). Median pooled OS was 7.86 (95%CI 7.01–8.72). The pooled overall response rate (ORR) was 8.63% (95%CI 6–11.26), and the pooled disease control rate (DCR) was 54.8% (95%CI 48.9–60.6). Median pooled OS with platinum- and pemetrexed-based chemotherapy were 7.93 and 7.78 months, respectively. Conclusions: There remains uncertainty about the ideal second-line agent for MPM. Based on this meta-analysis, palliative chemotherapy or other experimental agents can be considered for patients with MPM who desire further treatment after their disease has progressed, during or after first-line therapy. Highlights: Malignant pleural mesothelioma is treated with platinum/pemetrexed 1st line therapy. We performed a systematic review and meta-analysis of 49 s line studies. Median PFS and OS were 3.4 and 7.8 months. The pooled overall response rate was 8.6%. There remains uncertainty about the ideal second-line agent for pleural mesothelioma.